Porous ceramics
A ceramic porous body with controlled porosity and fiber composition achieves improved strength and durability by balancing porosity and density, addressing the challenge of lightweight yet robust ceramic materials.
Patent Information
- Application Number
- JP2021076912
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-29
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-04-29
AI Technical Summary
Porous ceramic bodies face a challenge in balancing porosity and strength, making it difficult to improve strength while maintaining lightness.
A ceramic porous body composed of ceramic particles and fibers with a specific porosity range (40% to 75%) and a dense surface layer, along with controlled porosity gradients and bimodal particle size distribution, ensures improved strength and lightness.
The solution enhances the strength and durability of the ceramic porous body while maintaining its lightweight properties, with excellent wear resistance and thermal stability.
Smart Images

Figure 0007610465000004 
Figure 0007610465000001 
Figure 0007610465000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a ceramic porous body. [Background technology]
[0002] A calcined alumina compact is known, which is obtained by mixing an aggregate of alumina fibers with a slurry in which the alumina fibers are dispersed in a specific solvent to obtain an alumina compact, and then calcining the alumina compact (e.g., Patent Document 1).A technique is also known in which a high-purity alumina fiber precursor is heat-treated, impregnated with the slurry, and then heat-treated again (e.g., Patent Document 2). Also known are a ceramic sintered body which is an aggregate of ceramic fibers and has high porosity (Patent Document 3), a ceramic porous body which is made by compression molding fibers and then heat treating them (Patent Document 4), and a ceramic material which is made by immersing long ceramic fibers in a ceramic slurry in which short ceramic fibers are dispersed (Patent Document 5). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-36034 A [Patent Document 2] Japanese Patent Application Publication No. 5-319949 [Patent Document 3] JP 2007-217235 A [Patent Document 4] JP 2011-219359 A [Patent Document 5] JP 2012-12240 A Summary of the Invention [Problem to be solved by the invention]
[0004] In ceramic porous bodies, porosity and strength are mutually exclusive properties, making it difficult to improve strength while maintaining light weight. The present disclosure has been made in view of the above-mentioned circumstances, and has an object to improve the strength of a ceramic porous body while ensuring its light weight. The present disclosure can be realized in the following forms. [Means for solving the problem]
[0005] [1] A ceramic porous body comprising one or more types of ceramic particles and one or more types of ceramic fibers, and having an average porosity of 40% or more and 75% or less, It has a dense surface layer, When the cross section of the ceramic porous body is observed in a field of view of 100 μm × 100 μm, Calculate the ratio P1 (%) of the area occupied by pores to the area of the field of view in a region within 100 μm from the surface of the ceramic porous body; In a region 200 μm or more away from the surface of the ceramic porous body, the ratio P2 (%) of the area occupied by pores to the area of the field of view is calculated as follows: A ceramic porous body, wherein the proportion P1 (%) is smaller than the proportion P2 (%) by 20% or more. Effect of the Invention
[0006] According to the present disclosure, it is possible to improve the strength of a ceramic porous body while ensuring its light weight. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a cross-sectional view that typically illustrates a cross section of a ceramic porous body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Here, a preferred example of the present disclosure is given. [2] A ceramic porous body, wherein when the particle size of the ceramic particles is measured in a region within 50 μm from the surface of the ceramic porous body, the particle size distribution exhibits a bimodal distribution.
[0009] [3] The ceramic particles are analyzed by energy dispersive X-ray analysis to calculate the content A (mass%) of the main elements constituting the ceramic particles in terms of oxides; The ceramic fiber is analyzed by energy dispersive X-ray analysis to calculate the content B (mass%) of the main elements constituting the ceramic fiber in terms of oxides. A ceramic porous body, wherein a main element constituting the ceramic particles and a main element constituting the ceramic fibers are the same, and the lesser of content A (mass%) and content B (mass%) is 70 mass% or more and 90 mass% or less.
[0010] [4] A ceramic porous body, wherein when a cross section of the ceramic porous body is observed over an area of 600 μm × 600 μm, the ceramic fibers having a fiber length of 50 μm or more have an average aspect ratio of 20 or more.
[0011] The present disclosure will be described in detail below. In this specification, a description using "~" for a numerical range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".
[0012] 1.Porous ceramics 1 The ceramic porous body 1 contains one or more types of ceramic particles and one or more types of ceramic fibers, and has an average porosity of 40% to 75%. The ceramic porous body 1 has a dense layer as a surface layer. When the cross section of the ceramic porous body 1 is observed in a field of view of 100 μm × 100 μm, the ratio P1 (%) of the area occupied by pores to the area of the field of view in a region within 100 μm from the surface of the ceramic porous body 1 is calculated, and the ratio P2 (%) of the area occupied by pores to the area of the field of view in a region 200 μm or more away from the surface of the ceramic porous body 1 is calculated. The ratio P1 (%) is smaller than the ratio P2 (%) by 20% or more.
[0013] (1) Ceramic particles Examples of ceramic particles include oxide-based ceramic particles, carbide-based ceramic particles, nitride-based ceramic particles, and carbonitride-based ceramic particles. The ceramic particles may be one type or two or more types. The ceramic particles are preferably oxide-based ceramic particles or carbide-based ceramic particles, and more preferably oxide-based ceramic particles. The ceramic particles preferably contain one or more oxides of elements selected from the group consisting of Al (aluminum), Mg (magnesium), Zr (zirconium), Si (silicon), Ti (titanium), Sr (strontium), Cr (chromium), and Ba (barium). Among these, the ceramic particles more preferably contain alumina (Al2O3) as a main component from the viewpoint of productivity. The ceramic particles also preferably contain silicon carbide (SiC) as a main component from the viewpoint of improving corrosion resistance.
[0014] The average particle size of the ceramic particles is not particularly limited. The average particle size of the ceramic particles may be, for example, 1 μm or more and 8 μm or less. The average particle size of the ceramic particles can be calculated as a circle equivalent diameter from a SEM (scanning electron microscope) image of the ceramic particles.
[0015] (2) Ceramic fibers Examples of ceramic fibers include oxide-based ceramic fibers and carbide-based ceramic fibers. The ceramic fibers may be one type or two or more types. The ceramic fibers are preferably oxide-based ceramic fibers or carbide-based ceramic fibers, and more preferably oxide-based ceramic fibers. The ceramic fibers preferably contain at least one selected from the group consisting of alumina (Al2O3) / silica (SiO2) fibers, alumina (Al2O3) fibers, silica (SiO2) fibers, and silicon carbide (SiC) fibers. Among these, the ceramic fibers more preferably contain alumina (Al2O3) / silica (SiO2) fibers from the viewpoints of productivity and toughness. The ceramic particles also preferably contain silicon carbide (SiC) fibers from the viewpoint of improving corrosion resistance. The ceramic fiber may be used in combination with inorganic fibers other than the ceramic fiber. An example of such an inorganic fiber is carbon (C) fiber. When the ceramic fiber and the inorganic fiber other than the ceramic fiber are used in combination, it is preferable that the content of the ceramic fiber is higher than the content of the inorganic fiber other than the ceramic fiber.
[0016] The average fiber length of the ceramic fibers is not particularly limited and may be, for example, 10 μm or more and 500 μm or less. The average fiber width of the ceramic fibers is not particularly limited and may be, for example, 10 μm or more and 50 μm or less. The average fiber length and width of ceramic fibers can be calculated from SEM images of ceramic particles. Specifically, as explained in (8) Requirements for the aspect ratio of ceramic fibers below, the fiber length and width of ceramic fibers with a fiber length of 50 μm or more are measured and the average value is calculated.
[0017] (3) Average porosity of ceramic porous body 1 The average porosity of the ceramic porous body 1 is 40% or more and 75% or less. From the viewpoint of light weight, the average porosity of the ceramic porous body 1 is 40% or more, preferably 50% or more, more preferably 60% or more, and further preferably 70% or more. Furthermore, if the average porosity of the ceramic porous body 1 is 75% or less, the strength of the ceramic porous body 1 can be ensured.
[0018] The average porosity of the ceramic porous body 1 can be calculated as follows. A 600 μm × 600 μm square region is identified on an SEM image of the cross section of the ceramic porous body 1. Image analysis is performed within this region using an EPMA (Electron Probe Micro Analyser) to determine the area of the entire region that is occupied by pores. The determined pore area is divided by the area of the region to calculate the porosity as a percentage. This porosity is determined in three different regions, and the average value is calculated. The calculated average value is the average porosity. The average porosity of the ceramic porous body 1 can be controlled by adjusting the size and amount of resin beads, the fiber length, fiber diameter and amount of the ceramic fiber raw material, the particle size and amount of the ceramic particle raw material, as well as the firing temperature and time, in the manufacturing method of the ceramic porous body 1 described below.
[0019] (4) Dense layer 2 The ceramic porous body 1 has a dense layer 2 as a surface layer. From the viewpoint of improving strength, abrasion resistance, and durability, it is more preferable that the entire surface layer of the ceramic porous body 1 exposed to the outside is the dense layer 2. The thickness of the dense layer 2 is not particularly limited. The thickness of the dense layer 2 may be greater than 0 μm, for example, 30 μm or more. The thickness of the dense layer 2 may be 200 μm or less, for example, 100 μm or less.
[0020] (5) Requirements regarding porosity difference When a cross section of the porous ceramic body 1 is observed in a field of view of 100 μm × 100 μm, the ratio P1 (%) of the area occupied by pores to the area of the field of view in a region within 100 μm from the surface of the porous ceramic body 1 is calculated, and the ratio P2 (%) of the area occupied by pores to the area of the field of view in a region 200 μm or more away from the surface of the porous ceramic body 1 is calculated. The ratio P1 (%) is 20% or more smaller than the ratio P2 (%). The region 200 μm or more away from the surface of the porous ceramic body 1 may be a region 300 μm or less, 500 μm or less, or 10,000 μm or less away from the surface of the porous ceramic body 1, depending on the size of the porous ceramic body 1. From the viewpoint of improving strength and abrasion resistance, the percentage P1 (%) is more preferably 22% or more smaller than the percentage P2 (%), and even more preferably 24% or more smaller. The percentage by which the percentage P1 (%) is smaller than the percentage P2 (%) is usually 55% or less, and may be 40% or less, or 35% or less. The difference between the proportions P1 (%) and P2 (%) can be controlled by adjusting the particle size of the raw material powder of the second ceramic particles, the blending ratio of the resin beads, etc. in the manufacturing method of the ceramic porous body 1 described below.
[0021] (6) Requirements for particle size distribution of surface layers It is preferable that the particle size distribution exhibits a bimodal distribution when the particle size of the ceramic particles is measured in a region within 50 μm from the surface of the ceramic porous body 1. With such a configuration, the porosity of the dense layer 2 can be further reduced, and the strength of the ceramic porous body 1 can be improved.
[0022] The particle size distribution in the region within 50 μm from the surface of the ceramic porous body 1 can be evaluated as follows. An SEM image of a cross section in which the normal direction to the surface of the ceramic porous body 1 is parallel to the cutting direction is obtained. On the SEM image, ten square regions of 50 μm × 50 μm are identified within 50 μm from the surface of the ceramic porous body 1. Image analysis is performed using EPMA within these regions to determine the particle size (circle equivalent diameter) of all ceramic particles. Regarding the particle size distribution of the ceramic particles, when at least one of (a) and (b) and (c) among the following requirements (a), (b), and (c) is satisfied, it is evaluated as exhibiting a bimodal distribution. It is even more preferable that the ceramic porous body 1 satisfies all of the requirements (a), (b), and (c). (a) The frequency of the lower of the two peaks is more than 0.55 times the frequency of the higher of the two peaks. (b) Only two peaks are observed. (c) The combined frequency of the two peaks accounts for 9% or more of the total frequency of ceramic particles.
[0023] For example, the ceramic porous body 1 may exhibit a bimodal particle size distribution consisting of a first peak having a peak top in the particle size range of 0.5 μm to 3 μm and a second peak having a peak top in the particle size range of 4 μm to 10 μm. Hereinafter, ceramic particles having a particle size larger than a predetermined value (e.g., 3.5 μm) may be referred to as first ceramic particles, and ceramic particles having a particle size equal to or smaller than the predetermined value may be referred to as second ceramic particles. The particle size distribution in the region within 50 μm from the surface of the ceramic porous body 1 can be controlled by adjusting the particle size of the raw material powder of the second ceramic particles in the manufacturing method of the ceramic porous body 1 described below.
[0024] (7) Requirements for the major elements of ceramic particles and ceramic fibers The content A (mass %) of the main element constituting the ceramic particle, calculated as an oxide, is calculated by analyzing the ceramic particle by energy dispersive X-ray analysis. Specifically, points on the ceramic particles in the cross section of the ceramic porous body 1 are analyzed by an energy dispersive X-ray analyzer (EDS) attached to the SEM. The point analysis is performed at five points located on different ceramic particles. All elements are quantitatively analyzed for each point, and the oxide-converted contents (mass%) of cationic components such as Al, Mg, and Si are calculated based on the analysis results. In this case, for example, Al is converted to Al2O3, Mg to MgO, Zr to ZrO2, Si to SiO2, Ti to TiO2, Sr to SrO, Cr to Cr2O3, and Ba to BaO. The oxide-converted contents of each cationic component are calculated by taking the total mass of all cationic components converted to oxides as 100 mass%. For each cationic component, the average content in terms of oxide obtained from the point analysis at five points is calculated. The cationic component with the largest average content is identified as the main element constituting the ceramic particle. The average value of the identified main element is then taken as the content A (mass%) in terms of oxide of the main element constituting the ceramic particle.
[0025] The content B (mass %) of the main element constituting the ceramic fiber, calculated as an oxide, is calculated by analyzing the ceramic fiber by energy dispersive X-ray analysis. Specifically, points on the ceramic fibers in the cross section of the ceramic porous body 1 are analyzed by an EDS attached to the SEM. The point analysis is performed at five points located on different ceramic fibers. All elements are quantitatively analyzed at each point, and the oxide-equivalent content (mass%) of cationic components such as Al and Si is calculated based on the analysis results. In this case, for example, Al is converted to Al2O3 and Si is converted to SiO2. The oxide-equivalent content of each cationic component is calculated with the total mass of all cationic components converted to oxide being 100 mass%. For each cationic component, the average content in terms of oxide obtained from the point analysis at five points is calculated. The cationic component with the largest average content is identified as the main element constituting the ceramic fiber. The average value of the identified main element is then taken as the content B (mass%) in terms of oxide of the main element constituting the ceramic fiber.
[0026] It is preferable that the main element constituting the ceramic particles is the same as the main element constituting the ceramic fibers. For example, when the main element constituting the ceramic particles is Al, it is preferable that the main element constituting the ceramic fibers is also Al. When the main element constituting the ceramic particles is Si, it is preferable that the main element constituting the ceramic fibers is also Si. The smaller of the content percentages A (mass%) and B (mass%) is preferably 70 mass% or more and 90 mass% or less. From the viewpoint of improving strength, the smaller of the content percentages A (mass%) and B (mass%) is more preferably 80 mass% or more. If the smaller of the content percentages A (mass%) and B (mass%) is 90 mass% or less, it is preferable in terms of improving the bonding strength of the interface between the ceramic particles and the ceramic fibers. When the main element constituting the ceramic particles is the same as the main element constituting the ceramic fibers, and the content A and content B are within the above ranges, the bonding strength of the interface between the ceramic particles and the ceramic fibers is improved by sintering. This is presumably because a reaction phase is formed at the interface between the ceramic particles and the ceramic fibers. Therefore, by satisfying the above requirements, the strength of the ceramic porous body 1 can be ensured even if the porosity of the ceramic porous body 1 is high. The types of main elements constituting the ceramic particles and ceramic fibers, and the contents A and B (mass%) of the main elements in terms of their oxides can be controlled by adjusting the types and amounts of the raw materials for the ceramic particles and ceramic fibers in the manufacturing method for ceramic porous body 1 described later.
[0027] (8) Requirements for the aspect ratio of ceramic fibers From the viewpoint of improving strength, when the cross section of the ceramic porous body 1 is observed in a field of view of 600 μm×600 μm, the ceramic fibers having a fiber length of 50 μm or more preferably have an average aspect ratio of 20 or more. The upper limit of the average aspect ratio is not particularly limited, but is usually 40 or less. It is presumed that the reason strength can be improved by satisfying this requirement is that the number of reaction sites between the ceramic particles and each ceramic fiber increases, and interaction between the ceramic fibers is also achieved.
[0028] The average aspect ratio of the ceramic fibers can be calculated as follows. A square region of 600 μm × 600 μm is identified on an SEM image of the cross section of the ceramic porous body 1. Image analysis is performed within this region using an EPMA to identify ceramic fibers with a fiber length of 50 μm or more. Ceramic fibers that extend beyond the field of view and have part of their outline not visible are excluded from the observation. For ceramic fibers with a fiber length of 50 μm or more, the fiber length and fiber width are measured, and the aspect ratio (fiber length / fiber width) is calculated. This aspect ratio is obtained in three different areas, and the average value is calculated. The above average aspect ratio can be controlled by changing the fiber length and fiber width of the ceramic fiber raw material, changing the conditions for mixing and grinding the raw material, etc. in the manufacturing method of the ceramic porous body 1 described later.
[0029] (9) Requirements for the percentage of area occupied by ceramic fibers When a cross section of the ceramic porous body 1 is observed over an area of 600 μm x 600 μm, it is preferable that the ratio of the area occupied by the ceramic fibers to the total area occupied by the ceramic particles and the area occupied by the ceramic fibers is 5.0% or more and 11.5% or less. From the viewpoint of ensuring strength, the ratio of the area occupied by the ceramic fibers is preferably 8.5% or more, more preferably 10% or more. If the ratio of the area occupied by the ceramic fibers is 11.5% or less, strength can be ensured and the variation in strength can be suppressed.
[0030] The percentage of the area occupied by the ceramic fibers can be calculated as follows. A 600 μm × 600 μm square area is identified on the SEM image of the cross section of the ceramic porous body 1. Image analysis is performed within this area using an EPMA to determine the area occupied by the ceramic particles and the area occupied by the ceramic fibers. The determined area occupied by the ceramic fibers is divided by the combined area occupied by the ceramic particles and the ceramic fibers to calculate the percentage of the area occupied by the ceramic fibers. The proportion of the area occupied by the ceramic fibers can be controlled by adjusting the sizes and compounding ratios of the raw materials of the ceramic particles and ceramic fibers in the manufacturing method of the ceramic porous body 1 described below.
[0031] 2. Method for producing ceramic porous body 1 There is no particular limitation on the method for producing the ceramic porous body 1. An example of the method for producing the ceramic porous body 1 will be described below.
[0032] (1) Raw materials The raw materials used are raw powder of ceramic particles (mainly the first ceramic particles) and raw fiber of ceramic fibers. In addition, resin beads are used to form pores. In addition, to form the dense layer 2, raw material powder of second ceramic particles is used.
[0033] (2) Granule production The raw powder of ceramic particles (mainly the first ceramic particles), the raw fiber of ceramic fibers, and resin beads are weighed out to a predetermined mixing ratio. The weighed raw materials, pebbles (e.g., Al2O3 balls), and a solvent (e.g., water) are placed in a container (e.g., a resin pot) and mixed and pulverized. The resulting slurry is dried to obtain granules.
[0034] (3) Molding The granules are press-molded to obtain a molded body.
[0035] (4) Coating A sol containing the raw material powder of the second ceramic particles is prepared. The surface of the molded body is coated with this sol by dipping. Instead of dipping, the sol containing the raw material powder of the second ceramic particles may be sprayed onto the molded body.
[0036] (5) Sintering The molded body coated with the raw material powder of the second ceramic particles is fired to obtain the ceramic porous body 1.
[0037] 3. Uses of Porous Ceramic Body 1 The use of the ceramic porous body 1 is not particularly limited. The ceramic porous body 1 is lightweight and has high strength, and is therefore suitable as a heat insulating material, a soundproofing material, and a buffer material. In addition, the ceramic porous body 1 has a high porosity and can contribute to improving the heat insulating performance of a heat insulating material. The ceramic porous body 1 has a high porosity and can contribute to improving the soundproofing performance of a soundproofing material. EXAMPLES
[0038] The present disclosure will now be described more specifically with reference to examples.
[0039] 1. Preparation of porous ceramics The ceramic particles (raw powder) used were various particles shown in the particle type column of Table 1. Of the particle types shown in Table 1, the particle type shown on the left side was blended in the largest amount. The ceramic fibers (raw fiber) used were various fibers shown in the fiber type column of Table 1. Among the fiber types shown in Table 1, the fiber type shown on the left side had the largest blending amount. 85 to 97 parts by mass of ceramic particles (raw powder) and 3 to 15 parts by mass of ceramic fibers (raw fiber) were mixed. Furthermore, 30 to 70 parts by mass of resin beads were mixed with respect to a total of 100 parts by mass of ceramic particles (raw powder) and ceramic fibers (raw fiber) to obtain a mixed powder. Water and polyvinyl alcohol (1 wt%) were added to this mixed powder and mixed and crushed. The mixed and crushed conditions were as follows: alumina balls, 20 rpm to 70 rpm, and 12 hours. After the mixed and crushed, the obtained slurry was dried to prepare granules. The obtained granules were press molded to prepare a molded body. The press molding conditions were: press pressure: 60 MPa, retention time: 10 seconds. The second ceramic particles (raw material powder) were the same as the particle type listed on the left side of Table 1, and had an average particle size of 3 μm or less. The surface of the compact was coated by dipping with a sol containing the raw material powder of the second ceramic particles. Then, the compact was fired to produce a ceramic porous body. The firing conditions were as follows: firing temperature: 1600°C, heating rate up to 600°C: 3°C / min, heating rate from 600°C: 10°C / min, holding time: 2 hours, in air.
[0040] [Table 1]
[0041] 2. Characteristics of Examples and Comparative Examples Table 2 shows the characteristics of each of the examples and comparative examples. The column "average porosity (%)" indicates the average porosity measured by the method described in "(3) Average porosity of ceramic porous body 1." The column for "Porosity Difference (%)" indicates the difference value obtained by subtracting the percentage P1 (%) from the percentage P2 (%) measured by the method described in "(5) Requirements for Porosity Difference." The column for particle size distribution in the surface layer shows the particle size distribution in the surface layer evaluated using the method described in "(6) Requirements for particle size distribution in the surface layer." Note that "〇" indicates that all of requirements (a), (b), and (c) are met. "△" indicates that among requirements (a), (b), and (c), (a) and at least one of (b) and (c) are met. "×" indicates that none of requirements (a), (b), and (c) are met. The column for the content A (mass%) of ceramic particles indicates the content A (mass%) of the main element constituting the ceramic particles, calculated as an oxide, measured by the method described in "(7) Requirements for the main element of the ceramic particles and the main element of the ceramic fibers." Note that the main element in the examples and comparative examples other than Example 4 is Al, and the main element in Example 4 is Si. The column for the ceramic fiber content B (mass%) indicates the content B (mass%) of the main element constituting the ceramic particles, calculated as an oxide, measured by the method described in "(7) Requirements for the main element of the ceramic particles and the main element of the ceramic fibers." Note that the main element in the examples and comparative examples other than Example 4 is Al, and the main element in Example 4 is Si. The average aspect ratio column indicates the average aspect ratio calculated using the method described in "(8) Requirements for the aspect ratio of ceramic fibers." The column for the lesser content (mass%) of A and B indicates the lesser content (mass%) of content A (mass%) and content B (mass%) measured by the method described in "(7) Requirements for the main elements of ceramic particles and the main elements of ceramic fibers."
[0042] [Table 2]
[0043] 3.Performance evaluation (1) Strength The bending strength of the ceramic porous bodies was measured in accordance with JIS R1664: 2004. The bending strength of the ceramic porous bodies was evaluated according to the following criteria. "☆": greater than 60MPa "◎": greater than 40MPa and less than 60MPa "○": greater than 20MPa and less than 40MPa “△”…20MPa or less
[0044] (2) Abrasion resistance In accordance with JIS R1613:2010, the abrasion test was carried out under the conditions of load: 1N, rotation speed: 10 rpm, abrasion material: aluminum, and time: 10 minutes, and the depth of the abrasion marks was measured. The depth of the abrasion marks was evaluated according to the following criteria. “◎”…10 μm or less "○": Larger than 10μm, 20μm or less "△": Larger than 20μm
[0045] (3)Durability The durability of the ceramic porous bodies was tested as follows. A thermal fatigue test was performed under conditions of a low temperature of 50°C, a high temperature of 250°C, and 500 thermal cycles. The bending strength of the ceramic porous bodies after the test was measured in accordance with JIS R1664:2004. The bending strength of the sample before the test was set as 100%, and the change (%) in bending strength of the sample after the test was calculated. The change (%) in bending strength of the sample after the test was evaluated according to the following criteria. "☆"...8% or less "◎": greater than 8% and less than 12% "○": greater than 12% and less than 18% "△": greater than 18%
[0046] 4. Evaluation Results The evaluation results are shown in Table 3. [Table 3]
[0047] Examples 1 to 20 satisfy the following requirements (a) and (b). Requirement (a): The average porosity is 40% or more and 75% or less. Requirement (b): The surface layer is a dense layer, and the percentage P1 (%) is 20% or more smaller than the percentage P2 (%). In Table 2, the difference between P2 (%) and P1 (%) is shown as the porosity difference.
[0048] In contrast, Comparative Examples 1 to 10 do not satisfy the following requirements. Comparative Example 1 does not satisfy the requirement (a). Comparative Example 2 does not satisfy the requirement (a). Comparative Example 3 does not satisfy the requirement (b). Comparative Example 4 does not satisfy the requirement (b). Comparative Example 5 does not satisfy the requirement (b). Comparative Example 6 does not satisfy the requirement (b). Comparative Example 7 does not satisfy the requirements (a) and (b). Comparative Example 8 does not satisfy the requirements (a) and (b). Comparative Example 9 does not satisfy the requirement (b). Comparative Example 10 does not satisfy the requirements (a) and (b).
[0049] Compared with Comparative Examples 1-10, Examples 1-20 had a good balance of strength, abrasion resistance, and durability. Among Examples 1 to 20, Examples 6 to 20, which further satisfied the following requirement (c), had higher strength and wear resistance. Among Examples 6 to 20, Experimental Examples 11 to 20, which further satisfied the following requirement (d), had higher durability. Among Examples 11 to 20, Experimental Examples 16 to 20, which further satisfied the following requirement (e), had even higher strength and durability. Requirement (c): When the particle size of ceramic particles is measured in a region within 50 μm from the surface of a ceramic porous body, the particle size distribution exhibits a bimodal distribution. Requirement (d): The main element constituting the ceramic particles and the main element constituting the ceramic fibers are the same, and the lesser of content A (mass%) and content B (mass%) is 70 mass% or more and 90 mass% or less. · Requirement (e): The average aspect ratio of the ceramic fibers is 20 or more.
[0050] 5. Effects of the embodiment The ceramic porous body of this example was able to improve strength while ensuring light weight. Furthermore, the ceramic porous body of this example was excellent in wear resistance and durability.
[0051] The present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present invention. [Explanation of symbols]
[0052] 1. Porous ceramics 2…Dense layer
Claims
1. A ceramic porous body comprising one or more types of ceramic particles and one or more types of ceramic fibers, and having an average porosity of 40% or more and 75% or less, It has a dense surface layer, When the cross section of the ceramic porous body is observed in a field of view of 100 μm × 100 μm, Calculate the ratio P1 (%) of the area occupied by pores to the area of the field of view in a region within 100 μm from the surface of the ceramic porous body; In a region 200 μm or more away from the surface of the ceramic porous body, the ratio P2 (%) of the area occupied by pores to the area of the field of view is calculated as follows: The proportion P1 (%) is smaller than the proportion P2 (%) by 20% or more, The ceramic particles are analyzed by energy dispersive X-ray analysis to calculate a content A (mass%) of a main element constituting the ceramic particles in terms of an oxide; The ceramic fiber is analyzed by energy dispersive X-ray analysis to calculate the content B (mass%) of the main elements constituting the ceramic fiber in terms of oxides. a main element constituting the ceramic particles and a main element constituting the ceramic fibers are the same, and the smaller of the content A (mass%) and the content B (mass%) is 70 mass% or more and 90 mass% or less, A ceramic porous body, wherein the dense layer has a thickness of 200 μm or less.
2. 2. The ceramic porous body according to claim 1, wherein when the particle diameters of the ceramic particles are measured in a region within 50 μm from the surface of the ceramic porous body, the particle size distribution exhibits a bimodal distribution.
3. 3. The ceramic porous body according to claim 1, wherein, when a cross section of the ceramic porous body is observed over an area of 600 μm×600 μm, the ceramic fibers having a fiber length of 50 μm or more have an average aspect ratio of 20 or more.
Citation Information
Patent Citations
Lightweight heat-resistant molded article and production thereof
JP1989278481A
Production of porous sintered form
JP1989286975A
Hybrid inorganic fibrous form
JP1990233568A
High toughness ceramic member
JP1993254950A
Production of alumina based fiber formed product
JP1993319949A